School Practices Control in Primary Education in Honduras (1882-1889) - García Lainez, Andrés Eduardo (Universidad Pedagógica y Tecnológica de Colombia, 2018)
A new chapter in History of Honduras was written as early as 1876: the Liberal Reform (1876-1905) led by the Marco Aurelio Soto Administration, initiating the Honduran State modernization process and being part of a wave of reformist governments that emerged in Latin America during the second half of the XIX century. The transformations in the education field during that period were primarily intended to develop an educational practice based on the positivist system proposed by the ideologist of this reform, Dr. Ramón Rosa, by means of the first Code of Public Instruction in 1882. In this context, the aim of this article is to analyze, from a Foucauldian perspective, the forms of school control through the exploration of regulations found in the first Code of Public Instruction and their articulation with school practices developed in primary education in Honduras between 1882 and 1889 that have been observed in the reports of school principals and inspectors of education. Four initial categories arise from this exercise in order to reflect on education in Honduras in the last two decades of the XIX century: teaching practice, teaching methods, school evaluation, and discipline.